Interplay of Dynamic Transcription and Chromatin Remodeling: Lessons from Yeast - Niederacher, Gerhard (Molecular Diversity Preservation International (MDPI), 2011)
Regulation of transcription involves dynamic rearrangements of chromatin structure. The budding yeast Saccharomyces cerevisiae has a variety of highly conserved factors necessary for these reconstructions. Chromatin remodelers, histone modifiers and histone chaperones directly associate to promoters and open reading frames of exposed genes and facilitate activation and repression of transcription. We compare two distinct patterns of induced transcription: Sustained transcribed genes switch to an activated state where they remain as long as the induction signal is present. In contrast, single pulsed transcribed genes show a quick and strong induction pulse resulting in high transcript levels followed by adaptation and repression to basal levels. We discuss intensively studied promoters and coding regions from both groups for their co-factor requirements during transcription. Interplay between chromatin restructuring factors and dynamic transcription is highly variable and locus dependent.